PENGEMBANGAN STRATEGI PEMBELAJARAN MELALUI MODEL KOOPERATIF TIPE GROUP INVESTIGATION BERBANTUAN FLIP CHART DALAM UPAYA MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS X MA NURUL IMAN DASAN MAKAM LOMBOK TIMUR - Hadratullah, Hadratullah; Martono, Trisno; Purwaningsih, Yunastiti (Jurnal Pendidikan Insan Mandiri, 2016)
The research was used Research and Development Approach (R&D). The procedure of the research was applied reffering to design and development research according to Borg and Gall that contained 6 steps of the development such as: (1) research and information collecting, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing, (7) operational product revision, (8) Operational field testing. The internal validation of learning strategy through cooperative learning type model Group Investigation using the Flip chart was involved the experts of learning, the experts of learning media, the experts of material and practitioner such as the economic teacher in this school.. Though, the external validation was done by tryout Learning strategy through cooperative learning type model Group Investigation using the Flip chart that involved the students of X IPS class. The subject of this research was the all of eleven grade social sciences MAN Nurul Iman Dasan Makam in academic year of 2014/2015 the total of the students was 44. In this research, the sample technique was taken by sampling population technique that was the technique to decide samples whether all member of population became the samples. The analysis technique data was used kualitatif descriptive, descriptive analysis and statistic inferential analysis.The result of the research showed that: (1) The learning strategies through cooperative learning type model Group Investigation using the Flip chart was stated valid based on the validity test by the experts, (2) The learning strategies through cooperative learning type model Group Investigation using the Flip chart was proved effective to be implemented in learning activity so that it could be to increase the economic study for students.,Keywords: learning strategy, learning models Group investigation, Flipchart, the result study of the students